Analisis Efisiensi Sistem Pemasaran Jagung di Provinsi Gorontalo (Studi Kasus pada Sentra Produksi Jagung di Kabupaten Pohuwato) - Isa, Ramlan Amir (Jurnal Aplikasi Manajemen, 2011)
The research aimed at testing and proving empirically: (1) knowing the corn distribution channel or flow of goods, since producer farmer to the final consumer of Gorontalo Provinice (2) Knowing the corn volume from each channel at Gorontalo Province. (3) Measuring the marketing margin distribution component at each marketing institution level at Gorontalo Province (5). Measuring the price correlation at consumer and producer levels to obtain the market integration level picture at corn marketing at Gorontalo Province. The results showed that: (1) The corn marketing at the research sites consist of three marketing distribution channel. From the three channel, there is main channel that channeling most of the marketing at the first marketing distribution channel, with cumulative volume of 61.075 tons. Based on three distribution channels, it was obtained the efficient relative channel, that is the second and third distribution channel, (2) The marketing margin at the research site of 25.98% so the producer farmer ger farmer's share of 74.02%, (3) The marketing cost and consumer price influence significantly but simultaneously influence of 78.6% while the remain was influenced by other variables that were not included in the model, (4) The correlation coefficient between price at the consumer level and price ar farmer level showed low value, it showed the integrated market condition, but the formed market structure was not full competitive market, (5) The elasticity value of price transmission that less than one reflected the marketing institution practice that direct to not full competitive market or oligosopny to the farmer. But with the low marketing margin value and the high farmer's share, then the formed corn marketing was efficient relative.